Beyond vascular recanalization: precision medicine in cervical artery dissection guided by multiple mechanisms and multimodal imaging for brain functional recovery - Li, Tao; Li, Linna; Zhao, Kexin; Dai, Jiaqi; Tian, Xueliang; Zhang, Xuanxiao; Yin, Shuo; Lan, Wenjing; Zhou, Hongwei (Frontiers in Physiology, 2026)
Cervical artery dissection (CAD), a critical etiological contributor of stroke in young adults, exerts direct influence on neurological prognosis through its vascular recanalization outcomes. However, pathological heterogeneity and ongoing controversies surrounding treatment strategies hinder the optimization of clinical decision-making; its prognosis is often not favorable. At present, there are a relative paucity of studies on recanalization of CAD. This review provides a concise overview of the pathological mechanisms and clinical challenges associated with CAD, along with recent advancements in advanced imaging modalities and clinico-anatomical classification systems. Furthermore, we critically evaluate current therapeutic paradigms and factors influencing recanalization while elucidating potential biological mechanisms underlying vascular restoration. A systematic analysis of translational utility in animal models is presented. Finally, based on the latest research progress in CAD and vessel recanalization, prospects are outlined aiming to establish a theoretical foundation for developing personalized and precise therapeutic approaches targeting CAD recanalization from multidimensional perspectives, and to offer reference for subsequent research.